Children and Adults Selectively Attribute Shared Cultural Knowledge to Speakers of the Same Language. Issue 1 (1st October 2018) - Soley, Gaye; Aldan, Pınar
Abstract : Children's and adults' attributions of shared knowledge of and shared preference for songs were investigated across two prominent social categories: language and gender. Both attributions indicate similarity among individuals but shared cultural knowledge can be more informative about common social history than shared preference, as it is mainly transferred through social interactions within cultures, while preferences can have various sources. Both 5‐ to 6‐year‐old children ( N = 60) and adults ( N = 160) generalized knowledge of songs across individuals who speak the same‐language rather than same‐gender individuals. In contrast, preference for songs was not systematically generalized across either category. Thus, individuals selectively infer shared cultural knowledge among same‐language speakers, suggesting an early emerging link between shared knowledge and cultural boundaries.